ANALISIS PEMBELAJARAN IPAS DALAM PEMBENTUKAN PERILAKU BERMORAL PESERTA DIDIK DI SEKOLAH DASAR - Febri Dwi Yanti; Badruli Martati; Fajar Setiawan (STKIP Subang, 2025)
This research aims to analyze the learning of IPAS (Integrated Science and Social Studies) in shaping the moral behavior of students at SD Muhammadiyah 2 Surabaya. The study employs a qualitative approach with descriptive qualitative methods. Data were collected through observations, interviews, and documentation. The results indicate that IPAS learning can be linked to moral education. Indicators of moral behavior include: (1) concern for others, (2) decision-making, (3) appreciation for diversity in the environment and society, (4) honesty and integrity, (5) empathy and social skills, and (6) responsibility and independence. IPAS learning on the topic of the struggles of national heroes through discussions about historical figures and important events provides students with the opportunity to understand the history of the nation's heroes while exploring the moral values contained within it to reflect on their actions. This article emphasizes the importance of integrating moral values into IPAS learning, which can shape students' moral behavior and be applied in everyday life.